2010
DOI: 10.1186/cc9058
|View full text |Cite
|
Sign up to set email alerts
|

Arterial pressure-based cardiac output in septic patients: different accuracy of pulse contour and uncalibrated pressure waveform devices

Abstract: IntroductionWe compared the ability of two devices estimating cardiac output from arterial pressure-curve analysis to track the changes in cardiac output measured with transpulmonary thermodilution induced by volume expansion and norepinephrine in sepsis patients.MethodsIn 80 patients with septic circulatory failure, we administered volume expansion (40 patients) or introduced/increased norepinephrine (40 patients). We measured the pulse contour-derived cardiac index (CI) provided by the PiCCO device (CIpc), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
94
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 39 publications
4
94
2
2
Order By: Relevance
“…Bolus transpulmonary thermodilution measurements are required for the estimation of these haemodynamic and pulmonary variables using the PiCCO. Several studies have investigated the accuracy of these values [17,[20][21][22]], but few have described the precision of this technique [23,24]. Accuracy refers to how close a measurement is to the actual or real value, and precision refers to how close repeated measurements are to each other [25].…”
mentioning
confidence: 99%
“…Bolus transpulmonary thermodilution measurements are required for the estimation of these haemodynamic and pulmonary variables using the PiCCO. Several studies have investigated the accuracy of these values [17,[20][21][22]], but few have described the precision of this technique [23,24]. Accuracy refers to how close a measurement is to the actual or real value, and precision refers to how close repeated measurements are to each other [25].…”
mentioning
confidence: 99%
“…Moreover, changes in vasomotor tone can impair the measurement performance of pulse contour analysis that might however be improved by frequent calibration to CO assessed with a more invasive technology (e.g. transpulmonary thermodilution) [16][17][18][19]. In addition, the proprietary pulse contour analysis algorithms consider biometric patient data or properties of the arterial pressure waveform to derive CO; in certain patients or clinical situations these mathematical assumptions might not hold true [19].…”
mentioning
confidence: 99%
“…The capacity of the uncalibrated FloTrac to estimate CO has been well established in surgical patients but has been seriously questioned by some studies in vasoplegic states [3][4][5][6]. For instance, the FloTrac did not allow tracking of the trends in CO in whom arterial pressure was modified by norepinephrine administration [6].…”
mentioning
confidence: 99%
“…For instance, the FloTrac did not allow tracking of the trends in CO in whom arterial pressure was modified by norepinephrine administration [6]. This suggested that the FloTrac estimation of CO was ''disorientated'' by large changes in arterial compliance and vasomotor tone, which might be problematic for septic shock patients and, more generally, for use in the intensive care unit.…”
mentioning
confidence: 99%
See 1 more Smart Citation